ПРОФЕСІЙНА ПІДГОТОВКА МАЙБУТНІХ ФАХІВЦІВ УПРАВЛІННЯ ЗАКЛАДАМИ ОСВІТИ НА ЗАСАДАХ МІЖДИСЦИПЛІНАРНОЇ ІНТЕГРАЦІЇ - РЕБУХА, Лілія (ГУМАНІТАРНІ СТУДІЇ : ІСТОРІЯ ТА ПЕДАГОГІКА, 2021)
У статті проаналізовано професійну підготовку майбутніх фахівців управління закладами освіти на засадах міждисциплінарної інтеграції, так як суспільство ставить особливі вимоги до керівника та набуття ним під час навчання в магістратурі дієвих управлінських компетентностей. Проведено аналіз наукових праць, що дозволило виокремити проблеми (загальні та професійні), які нині існують у навчанні майбутніх фахівців-управлінців за університетської освіти. Для забезпечення інноваційного розвитку педагогічної системи та її найкращого функціонування запропоновано здійснювати підготовку магістрів спеціальності 011 «Освітні, педагогічні науки» освітньо-професійної програми «Управління навчальними закладами» відповідно до міждисциплінарної інтеграції. Доведено, що за використання в освітньому процесі студентів міждисциплінарної інтеграції сприяє єдності теоретико-методологічної, загальноосвітньої і практично-спрямованої професійної підготовки, яка спрямована на цілісне формування міждисциплінарних знань, розвиток дослідницьких умінь і навичок. Виокремлено головний зміст навчання на засадах міждисциплінарної інтеграції, що віднайшло своє відображення в окреслених вимогах до професійної підготовки магістра з управління закладами освіти в університеті. Обґрунтовано, що дотримання в освітньому процесі загальнометодологічних принципів (цілісності, системності, структурованості, багаторівневості, відповідності) дозволяє розглядати міждисциплінарну інтеграцію як цілісний процес взаємодії, синтезу, взаємопроникнення навчальних дисциплін у зміст професійної підготовки майбутніх управлінців закладів освіти шляхом впровадження викладачем дієвих засобів інноваційних педагогічних технологій. Зазначена необхідність впровадження у процес підготовки магістрів з управління закладом освіти міждисциплінарної інтеграції сприяє встановленню усвідомленого взаємозв’язку вивченого з майбутньою професійною діяльністю. Внаслідок цього в освітньому процесі на всіх рівнях (на рівні вивчення навчальної теми з окремої дисципліни; на рівні освоєння тем, що входять до навчального модуля; на рівні вивчення навчальної дисципліни в цілому; на рівні навчальних дисциплін, що вивчаються студентами впродовж навчання в магістратурі) значно оптимізуються результати освітнього процесу. The article analyzes the professional training of future specialists in the management of educational institutions on the basis of interdisciplinary integration, since society imposes special requirements on the leader and the acquisition of effective managerial competencies during their studies in the master’s program. The analysis of scientific works was carried out, which made it possible to highlight the problems (general and professional) that now exist in the training of future managerial specialists in university education. To ensure the innovative development of the pedagogical system and its better functioning, it is proposed to train masters of specialty 011 «Educational, pedagogical sciences» of the educational and professional program «Management of educational institutions» on interdisciplinary integration. It is proved that, when used in the students’ educational process, interdisciplinary integration contributes to the unity of theoretical-methodological, general educational and practical-oriented professional training, which is aimed at the holistic formation of interdisciplinary knowledge, the development of research skills and abilities. The main content of training is highlighted on the basis of interdisciplinary integration, which is reflected in certain requirements for the professional training of a master in management of educational institutions at the university. It is substantiated that the observance in the educational process of the methodological principles (integrity, consistency, structuredness, multilevel, conformity) allows us to consider interdisciplinary integration as an integral process of interaction, synthesis, interpenetration of academic disciplines into the content of professional training of future managers of educational institutions through the introduction of effective means of innovative pedagogical technologies by the teacher. The indicated need to introduce interdisciplinary integration into the process of training masters in management of an educational institution contributes to the establishment of a conscious relationship between the studied and future professional activities. As a result, in the educational process at all levels (at the level of studying the academic topic from a separate discipline, at the level of mastering the topics that are included in the educational module, at the level of studying the academic discipline as a whole, at the level of academic disciplines studied by students during their master’s studies) the results of the educational process are significantly optimized.